Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/jper.20-0713
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a novel non‐invasive application of platelet‐rich fibrin on periodontal clinical parameters and gingival crevicular fluid transforming growth factor‐β and collagen‐1 levels: A randomized, controlled, clinical study

Abstract: Background Several potential benefits have been attributed to the platelet‐rich fibrin (PRF), including enhanced tissue healing properties. In this study, we hypothesized that the application of PRF as an adjunct to conventional scaling and root planing (ScRp) would enhance the outcomes of non‐surgical periodontal therapy. Methods The present study was a split‐mouth randomized controlled clinical trial design in 24 deep periodontal pockets in 12 patients with periodontitis. The pockets were randomly assigned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Özcan, E.,et al showed that the average of PPD at sites treated with ScRp+PRF were 2.57 ± 0.75 mm at 3 months. 26 The bolded numbers refer to statistically significant differences (p < 0.05 and p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Özcan, E.,et al showed that the average of PPD at sites treated with ScRp+PRF were 2.57 ± 0.75 mm at 3 months. 26 The bolded numbers refer to statistically significant differences (p < 0.05 and p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…control groups which were 2.57 ± 0.75 and 0.93 ± 0.49 mm respectively. 26 For sample size calculation, G power software (v. 3.1.9.6) was used with 95% confidence interval and margin of error of 5%.…”
Section: öZcan Et Al Calculated the Means Of Pocket Reduction Of Test...mentioning
confidence: 99%
“…To date, hyaluronic acid and enamel matrix derivatives have been registered as medical devices under FDA, whereas, aPDT used in dentistry comprises of a chemical agent (photosensitizer dye) and a medical device (laser) component. Recently, biological mediators such as polypeptide growth factors have also been introduced for use as an adjunct in nonsurgical periodontal therapy [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…During periodontal tissue regeneration, collagen-type-I (COL1A1) 17 and periostin (POSTN) 18 play a crucial role, while vascular endothelial growth factor (VEGF) 19 and angiogenin (ANG) 20 are known for their importance in angiogenesis and finally interleukin (IL)6 and IL8 21 mediate the periodontal inflammatory process. Thus, it is of utter importance for material development in periodontal GTR to understand which in vitro model is the most suitable to test novel or optimized membranes and bone substitute materials in terms of regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, an in vitro model for GTR research that mimics patient‐side periodontal ligament should not only be a 3D construct, but also be capable to deliver information on biocompatibility, cell adhesion and production of molecular biomarkers for regeneration, angiogenesis and inflammation. During periodontal tissue regeneration, collagen‐type‐I (COL1A1) 17 and periostin (POSTN) 18 play a crucial role, while vascular endothelial growth factor (VEGF) 19 and angiogenin (ANG) 20 are known for their importance in angiogenesis and finally interleukin (IL)6 and IL8 21 mediate the periodontal inflammatory process. Thus, it is of utter importance for material development in periodontal GTR to understand which in vitro model is the most suitable to test novel or optimized membranes and bone substitute materials in terms of regeneration.…”
Section: Introductionmentioning
confidence: 99%